Civil Rights Of Children Outside Married Due Isbat Nikah Of Polygamy (Analysis of Islamic Court of Rembang Decision No. 99 / Pdt.G / 2018 / PA.Rbg.) - Rofi'atun Rofi'atun; Akhmad Khisni; Rozihan Rozihan (Jurnal Daulat Hukum, 2019)
This study discusses the civil rights of children outside the mating due to confirmation of marriage polygamy, Problems taken author in this thesis is how the legal protection of children outside marriage related his civil rights especially on custody of marriage and inheritance rights to men as fathers biological, because the Indonesian Constitution the Act of 1945 and other regulations related to children's rights requires such a case, article 28 B (2) the result of amendments to the Act of 1945 states "Every child has the right to live, grow and develop and is entitled to protection from violence and discrimination, as well as the norms of Islamic law every child born in the holy predicate attached to him (Fitrah), so that the civil rights of Islam also guaranteed, regardless of whether the child was born out of and / or as a result of a legal marriage or a result of Sirri Marriage.The research method used by writer is a normative juridical approach where the study was conducted based on legal materials main by way of studying the theories, concepts, principles of law, rule of law, court decisions and legislation relating to this study.The results showed that based on the decision number: 99 / Pdt.G / 2018 / PA.Rbg, in the case of confirmation polygamous marriage, civil rights children outside marriage (polygamy) or Sirri equal to the rights of children born and / or result polygamous marriage is official, so that the legal rights of children outside marriage in the decision on child custody and inheritance rights equal to other biological children were born of the first marriage. thus based on the decision of the civil rights of children protected by law, to get justice, and the certainty of the status and civil rights.Keywords: Civil Rights of Children Outside Marriage; Sirri Polygamy; Rights of Guardianship And Inheritance.